Educação na Federação Brasileira: federalismo, laicidade e religião - Carlos Henrique de Carvalho; Wenceslau Gonçalves Neto (Universidade Estadual de Maringá, 2016)
Acta Scientiarum. Education v. 38, n. 2, 2016